Kathmandu, Patan and Bhaktapur by Dr Rishikeshab Raj Regmi - Jha, Hemant Kumar (Occasional Papers in Sociology and Anthropology, 2008)
Kathmandu, Patan and Bhaktapur by Dr Rishikeshab Raj Regmi Nirala Publications, New Delhi. DOI: 10.3126/opsa.v4i0.1090 Occasional Papers in Sociology and Anthropology Vol.4 1994 p.146-149